Pengaruh Pengetahuan Perpajakan, Tarif Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Kecamatan Ciomas - Ramadhany, Tsaltsa Putri; Rumiasih, N.A; Yudiana, Yudiana (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to examine the Influence of Tax Knowledge, Tax Rates, and Tax Sanctions on the Compliance of MSME Taxpayers in the Ciomas District. This study uses a quantitative approach with primary data sources obtained from questionnaire distribution. The sample in this study amounted to 55 MSMEs, which were selected using simple random sampling method. The data analysis technique used is multiple linear regression analysis processed using SPSS 26. The results of the study indicate that Tax Knowledge has a positive effect on the Compliance of MSME Taxpayers in the Ciomas District, Tax Rates do not affect the Compliance of MSME Taxpayers in the Ciomas District, and Tax Sanctions have a positive effect on the Compliance of MSME Taxpayers in the Ciomas District.